Atomical Reconstruction and Cationic Reordering for Nickel‐Rich Layered Cathodes. Issue 11 (29th January 2022) - Ni, Lianshan; Chen, Hongyi; Deng, Wentao; Wang, Baowei; Chen, Jun; Mei, Yu; Zou, Guoqiang; Hou, Hongshuai; Guo, Rui; Xie, Jingying; Ji, Xiaobo
Abstract: Capacity fading and safety concerns accompanied other deep‐rooted challenges have severely hindered commercial development of Ni‐rich layered cathodes. Herein, a robust Sr‐doped Ni‐rich cathode is structurally designed by the reconstruction of the crystal lattice and electronic distribution. Notably, the orbital hybridization between Ni 3d (t2g ) and O 2p is remarkably reinforced owing to the shortened NiO bond enabled by the electrostatic interaction between Ni and Sr atoms, giving rise to the enhanced crystal structure. Theoretically, the formation energy of oxygen vacancies is greatly increased due to the intensified electronic polarization between Ni and O states evoked by the weak electronegativity of Sr, resulting in the alleviation of lattice oxygen loss. More impressively, the distances of LiO bonds and the OLiO slab are also extended on account of the electrochemically inactive Sr ion functioning as a pillar, further promoting the transmission of lithium ions. Therefore, the as‐designed Sr‐modified NCM delivers an ultrahigh capacity retention of 98.5% after 150 cycles. This work provides a powerful mechanistic incentive to increase the stability of the crystal phase and electrochemical performance for Ni‐rich layered cathodes through appropriate chemical and mechanical engineering, facilitating the practical applications of Ni‐rich cathodes in high‐performance electric vehicles. Abstract : Capacity fading and safety concerns accompanied by other deep‐rooted challenges have severely hindered commercial development of Ni‐rich layered cathodes. A robust Sr‐doped Ni‐rich cathode is structurally designed to alleviate the deep‐rooted particle microcracking and surface phase transitions by the reconstruction of the crystal lattice and electronic distribution through the introduction of Sr ions into the bulk phase.